Syllable structure - Jakobsen Per (Južnoslovenski Filolog, 2008)
In traditional structuralist understanding, language is a system of signs i.e. an inseparable unity of content and expression. According to glossematic linguistic theory, the dichotomy of form and substance in the content has its parallel in the expression. The present paper shows that in one language certain consonant clusters within the syllable are allowed, in other languages they are not. The phonotactic structure, i.e. the rules of forming syllables decide the forming of new words and identify the language at the same time. This fundamental syllable structure shows that it is scientifically untenable to maintain that the Serbo-Croatian language has split up in several new languages. .